Culture - civilization: A comparison between Japan and Vietnam - Yumio, Sakurai (Vietnam National University, Hanoi, 2020)
According to perception of historical area study, civilization and culture should be differentiated clearly. Culture was born in a certain environment to life techniques respond it. Civilization was formed to over its environmental limit. West Japan and North Vietnam co share same natural environment such as complex of small deltas and mountains under sub-tropical temperature. West Japanese traditional culture originated at Yayoi period is very similar to north Viet culture originated at Dong Son time. Through history, those two cultures with the same origin had been influenced deeply by North Chinese Classic Civilization and South Chinese rice cropping culture.